The Factors Influencing Students' Interest In Accounting Career In Sharia Bank: Case Study of Undergraduate Accounting Students from Higher Education in Jember - Nada Atika, Hulwun; Sita Nastiti, Ari; Halim, Moh (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
The purpose of this research is to determine the factors that influence accounting students' interest in pursuing a career at a sharia bank (case study of undergraduate accounting students at universities in Jember) and the variables used in this research are work environment, financial rewards, religiosity and accounting knowledge on career interest. at a sharia bank. The population in this study was from several campuses in Jember, namely Muhammadiyah University Jember, Jember University, Kiai Haji Achmad Siddiq State Islamic University Jember and Mandala Institute of Science and Technology Jember. The technique used in this research is Non Probability Sampling with the Purposive Sampling method. The data collection technique used in the research was a questionnaire and was distributed to students who were used as the population and the sample used was 135 students. The results of the research explain that the variables Work Environment and Religiosity have a significant effect on students' interest in working in sharia banks and the variables Financial Reward and Accounting Knowledge do not have a significant effect on career interest in sharia banks. Meanwhile, all variables together have a significant effect on interest in a career in sharia banking.